Location of the Cell Adhesion Molecule “Coxsackievirus and Adenovirus Receptor” in the Adult Mouse Brain - Wehbi, Amani; Kremer, Eric J.; Dopeso-Reyes, Iria G. (Frontiers in Neuroanatomy, 2020)
The coxsackievirus and adenovirus receptor (CAR) is a single-pass transmembrane cell adhesion molecule (CAM). CAR is expressed in numerous mammalian tissues including the brain, heart, lung, and testes. In epithelial cells, CAR functions are typical of the quintessential roles of numerous CAMs. However, in the brain the multiple roles of CAR are poorly understood. To better understand the physiological role of CAR in the adult brain, characterizing its location is a primordial step to advance our knowledge of its functions. In addition, CAR is responsible for the attachment, internalization, and retrograde transport of canine adenovirus type 2 (CAV-2) vectors, which have found a niche in the mapping of neuronal circuits and gene transfer to treat and model neurodegenerative diseases. In this study, we used immunohistochemistry and immunofluorescence to document the global location of CAR in the healthy, young adult mouse brain. Globally, we found that CAR is expressed by maturing and mature neurons in the brain parenchyma and located on the soma and on projections. While CAR occasionally colocalizes with glial fibrillary acidic protein, this overlap was restricted to areas that are associated with adult neurogenesis.